Regional/national forecast of prices of different fuels - Murat Albegov (European Regional Science Association (ERSA), 1998)
Calculation of spacely- divided national fuel-power model stimulated an investigation the rules of formation of marginalal costs. Such notions as marginal fiel of the country, marginal consumer of particular fuel and etc. Are introduced and quantatively illustrated. Analysis of the main international fuel-energy flows whithin energy-unified groups of countries gives the key to calculation the prices of fuel and energy.For the european zone (including Arab countries, North Africa and european part of Russia) the prices of oil,gas and coal in all regions (centers) of european part of Russia and Siberea were calculated for the prospective up to 2010 year. All calculated figures are shown. The main and the only exogenous figure for this forecast -the price of oil barrel in tne centre of Europe. rope.
Keywords: 330